Characteristics Analysis and Optimum Design of Small Size Thrust Air Bearing for HDD-Application to Optimum Design - Namba, T.; Ibrahim, M.D; Ochiai, M.; Hashimoto, H. (2008)
Grooved thrust air bearings are widely used for lightly loaded and very high speed machinery. HDD is one of the applications of the machinery. Recently, larger storage capacity and higher transfer speed for HDD is required, hence hydrodynamic oil bearings are adopted. However it has several problems such as high friction torque and low bearing stiffness due to vary the oil viscosity by changing the temperature. In this way, thrust air bearings which make up for the faults is very suitable. However, generally, the stiffness of thrust air bearings is low. Therefore in the design of thrust air bearings, it is important to maximize the stiffness of air film. In this paper the optimum design of groove geometry for small size thrust air bearing to maximize the dynamic stiffness of air film is described and the vibration analysis is conducted to confirm the adaptability and the effectiveness of optimization.